PELATIHAN MANAJEMEN BISNIS DAN WIRAUSAHA PADA INDUSTRI LOGAM PANDAI BESI KABUPATEN WAKATOBI DI PULAU BINONGKO - Inayah Abdillah Rabbani; An Najjar M. Thahir (Jurnal Pengabdian Masyarakat Sabangka, 2023)
Business management and entrepreneurship training is one of the efforts to equip small and medium industry (SMI) players in ensuring the sustainability of the business they run to generate economic value consistently. The training attended by 30 participants of metal industry players in Wakatobi Regency aims to improve the ability and skills of business management and entrepreneurship management so that it can be run adequately, competitively and develop by understanding the principles of entrepreneurship management properly. This training implements the Training Need Analysis (TNA) method which is compiled from the work program of the Wakatobi Regency Industry and Trade Service. The material given to participants uses the blended system method with an allocation of 40 percent theory, 40 percent practice, and 20 percent discussion and questions – answers. The implementation of this training shows an increase in the percentage of participants' understanding of business management and entrepreneurship based on the pretest results below 50 percent increasing to above 50 percent in the posttest results, as well as the ability to solve cases from each material package - practice and the ability to complete daily quizzes.